Association of anticardiolipin IgM antibody with preeclampsia (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The objective of this study was to evaluate association of anticardiolipin IgM antibody with preeclampsia among the 70 pregnant women having preeclampsia from March 2016 to February 2017. Equal number of age matched normotensive healthy pregnant women was selected as control. Demographic, obstetric and relevant laboratory data were collected and compared between the two groups. The level of anticardiolipin IgM antibody was significantly higher in preeclamptic women than in normal pregnant (mean 8.7 vs 5.8 U/mL, p